Entry of dengue virus serotypes and their geographic distribution in Brazilian federative units: a systematic review - Juliana Maria Trindade Bezerra; Selma Costa de Sousa; Pedro Luiz Tauil; Mariângela Carneiro; David Soeiro Barbosa (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2021)
Objective: To describe the entry of Dengue virus (DENV) serotypes in Brazil and its federative units. Methods: A systematic review of studies published between 1980 and 2018 in databases and in the gray literature was performed using descriptors related to the years of entry of the DENV serotypes. Additionally, experts and official sources of information (Brazilian Ministry of Health) were consulted. Results: From 100 publications selected for the systematic review, 26 addressed the entry of DENV serotypes in the North region of the country, 33 in the Northeast, 24 in the Southeast, 14 in the Central-West, and five in the South. DENV-1 and DENV-4 were introduced in the North region in 1981. DENV-2 was introduced in the Southeast in 1990. DENV-3 was introduced in the North in 1999. Conclusion: The rapid expansion of dengue throughout the Brazilian territory was verified from the second half of the 1980s, with the gradual entry of the four serotypes, which resulted in the emergence of epidemics of arbovirus, which are currently verified in the country. Considering the epidemiology of the disease, more information should be disseminated and published in the wide-ranging scientific literature for a better understanding of the spread and circulation of DENV serotypes.